Computational Modeling of a Low‐Cost Fluidic Oscillator for Use in an Educational Respiratory Simulator. Issue 12 (14th November 2021) - Dillon, Tom; Ozturk, Caglar; Mendez, Keegan; Rosalia, Luca; Gollob, Samuel Dutra; Kempf, Katharina; Roche, Ellen Tunney
Abstract : Herein, the computational modeling of a fluidic oscillator for use in an educational respiratory simulator apparatus is presented. The design provides realistic visualization and tuning of respiratory biomechanics using a part that is (i) inexpensive, (ii) easily manufactured without the need for specialized equipment, (iii) simple to assemble and maintain, (iv) does not require any electronics, and (v) has no moving components that could be prone to failure. A computational fluid dynamics (CFD) model is used to assess flow characteristics of the system, and a prototype is developed and tested with a commercial benchtop respiratory simulator. The simulations show clinically relevant periodic oscillation with outlet pressures in the range of 8–20 cmH2 O and end‐user‐tunable frequencies in the range of 3–6 s (respiratory rate [RR] of 10–20 breaths per minute). The fluidic oscillator presented here functions at physiologically relevant pressures and frequencies, demonstrating potential as a low cost, hands‐on, and pedagogical tool. The model will serve as a realistic model for educating Science, Technology, Engineering, and Mathematics (STEM) students on the relationship between flow, pressure, compliance, and volume in respiratory biomechanics while simultaneously exposing them to basic manufacturing techniques. Abstract : The computational modeling of a fluidic oscillator designed to convert continuous positive airway pressure (CPAP) machines into emergency mechanical ventilators is presented. The oscillator addresses potential ventilator shortages using a part that is inexpensive and easily manufactured. The fluid dynamics model is used to assess system performance, and a prototype is tested using a benchtop respiratory simulator.